Relating Large Amplitude Oscillatory Shear and Food Behavior: Correlation of Nonlinear Viscoelastic, Rheological, Sensory and Oral Processing Behavior of Whey Protein Isolate/κ‐Carrageenan Gels. Issue 4 (7th March 2013) - Melito, H.S.; Daubert, C.R.; Foegeding, E.A.
Abstract Creating desirable food textures begins with a fundamental understanding of texture, which involves measuring mechanical properties of the food product. Large strain mechanical properties have been correlated with sensory and oral processing characteristics; however, most large strain testing in food research involves determination of fracture properties rather than examination of nonlinear viscoelastic behavior. Relationships between nonlinear viscoelastic behavior and food texture were determined by measuring and correlating nonlinear viscoelastic properties of several whey protein isolate/κ‐carrageenan gels to sensory, oral processing and large strain rheological characteristics. Nonlinear viscoelastic properties correlated (R2 > 0.5, P < 0.05) to sensory, oral processing and large strain rheological behaviors. Sensory correlations included aspects evaluated after several chews as well as first bite aspects. Oral processing correlations generally involved jaw movement terms rather than electromyographical data. Understanding the nonlinear viscoelastic properties of food allows a better understanding of food structure and deformation mechanism and how that structure impacts food texture. Practical Applications This work demonstrates the applicability of large amplitude oscillatory shear (LAOS) testing in food science. The LAOS measurement and analysis method may be applied to foods with a wide range of structure and texture, allowing measurements of nonlinear viscoelastic behavior in materials that cannot be tested under current methodology. In addition, LAOS measurements can indicate structural aspects of the material, and correlations between structure and texture may be made from this information.